A Study on the Relationship between Personality and Driving Styles - Poó, Fernando Martín (2013)
Objective: Research on driving behavior and personality traits is a key factor in the development of driver-oriented safety interventions. However, research is fragmented and a multidimensional perspective is lacking. The primary aim of this study is to assess the multiple relationships between driving styles and personality traits using the alternative 5-factor model. A secondary goal is to determine whether these relationships vary by gender and age. Methods: Data were collected from a sample of 908 Argentine drivers. Driving styles were assessed using the Multidimensional Driving Style Inventory. Personality was assessed with the Zuckerman-Kuhlman Personality Questionnaire (ZKPQ-50-CC; Aluja et al. 2006) questionnaire. Results: Different patterns of personality are associated with different driving styles. These relationships appear to be robust with respect to gender and age; however, in some cases these variables did influence the observed relationships. Conclusion: The results provide researchers with a more comprehensive understanding of the relationships between personality traits and driving styles. Practical prevention measures are discussed